BUDAYA ORGANISASI SEBAGAI PREDIKTOR ORGANIZATIONAL CITIZENSHIP BEHAVIOR DI PT. PRIMAYUDHA MANDIRIJAYA, BOYOLALI - Faiz Deaky Febrianto; Sutarto Wijono (Journal of Innovation Research and Knowledge, 2024)
The aim of this study is to determine the role of organizational culture as a predictor of organizational citizenship behavior (OCB) among production employees at PT. Primayudha Mandirijaya. This research employs a quantitative research method. The study was conducted on production employees at PT. Primayudha Mandirijaya in Boyolali. The population of the study amounted to 1236 individuals, with a sample size of 93 individuals determined using random sampling techniques and the Slovin formula. The research instrument was an organizational culture scale adapted from the scale developed by Denison in Nisa (2021), based on four aspects of organizational culture, with a reliability value of 0.948 and validity index values ranging from 0.469 to 0.684. Additionally, an organizational citizenship behavior (OCB) scale developed by Organ in Dewi (2021) was used, based on five aspects of organizational citizenship behavior (OCB), with a reliability value of 0.828 and validity index values ranging from 0.406 to 0.500. Hypothesis testing yielded results of R2 = 0.684; p < 0.05. These findings indicate that organizational culture (X) is a predictor of organizational citizenship behavior (Y) among production employees at PT. Primayudha Mandirijaya.